Herpesviruses mimic zygotic genome activation to promote viral replication - Neugebauer, Eva; Walter, Stephanie; Tan, Jiang; Drayman, Nir; Franke, Vedran; van Gent, Michiel; Pennisi, Sandra; Veratti, Pia; Stein, Karla S.; Welker, Isabelle; Tay, Savaş; Verjans, Georges M.G.M.; et al. (Nature Communications, 2025)
Zygotic genome activation (ZGA) is crucial for maternal to zygotic transition at the 2-8-cell stage in order to overcome silencing of genes and enable transcription from the zygotic genome. In humans, ZGA is induced by DUX4, a pioneer factor that drives expression of downstream germline-specific genes and retroelements. Here we show that herpesviruses from all subfamilies, papillomaviruses and Merkel cell polyomavirus actively induce DUX4 expression to promote viral transcription and replication. Analysis of single-cell sequencing data sets from patients shows that viral DUX4 activation is of relevance in vivo. Herpes-simplex virus 1 (HSV-1) immediate early proteins directly induce expression of DUX4 and its target genes, which mimics zygotic genome activation. Upon HSV-1 infection, DUX4 directly binds to the viral genome and promotes viral transcription. DUX4 is functionally required for infection, since genetic depletion by CRISPR/Cas9 as well as degradation of DUX4 by nanobody constructs abrogates HSV-1 replication. Our results show that DNA viruses including herpesviruses mimic an embryonic-like transcriptional program that prevents epigenetic silencing of the viral genome and facilitates herpesviral gene expression.
CRIS-Team Scopus Importer:2025-01-31